Digital signal processing using Matlab - Ingle, Vinay K.; Proakis, John G. (Pacific Grove : Brooks/Cole, 2000)
Discrete-time signals and systems; The discrete-time fourier analysis; The z-transform; The discrete fourier transform; Digital filter structures; Fir filter design; IIR filter design; Applications in adaptive filtering; Applications in communications.
Includes bibliographical references.
Keywords: Signal processing; Signal processing -- Digital techniques -- Mathematics; MATLAB